Penggunaan Electronic Medication Management (EMM) dalam Menurunkan Kejadian Medication Error di Keperawatan - Siti Indriani (Universitas Muhammadiyah Lamongan, 2020)
Errors in drug administration are adverse events for patients. Reducing the incidence of medication errors will significantly improve patient safety and quality of medication use. The traditional system makes staff spend time searching through notes on a compilation paper of what drugs patients must pay throughout the treatment process that is given. This process is not only lengthy, but also can easily increase opportunities for differences and mistakes. Many hospitals and health services are turning to digital systems as a solution. The EMM system supports the improvement of quality, safety, and support for drug management in hospitals. This includes providing support for doctors, nurses and pharmacists to prescribe, order, accept, reconcile, issue and install digital drug administration. EMM covers the entire treatment cycle in the hospital including prescribing by doctors, approved and issued drug orders by pharmacists, and administration of drugs by nurses. The use of EMM can provide benefits that are improving the quality of patient-oriented nursing care, the quality of clinical services and the use of information technology. Nurses as health workers with the largest